Knowledge of Study Tourism and Reconstruction of Community Residents' Place Identity: A Case Study of Danxia Mountain Nature Protected Area, Guangdong - Yang Jirong; Zhang Chaozhi (Redai dili, 2024)
Promoting community engagement is a key issue in the sustainable development of protected natural areas. Enhancing the local residents' sense of place identity contributes to their willingness to protect the ecological environment and increases their support for ecotourism development. The role of knowledge in addressing ecological issues is widely recognized, and tourism, which focuses on knowledge production and dissemination, is gradually emerging as an alternative choice for innovative and sustainable ecotourism development in protected natural areas. However, the effect of knowledge on place identity has not been sufficiently addressed. This study employed a qualitative research method and considered Danxia Mountain, a protected area, as a case study to analyze the transformation of knowledge underlying tourism products during the transition from sightseeing tourism to study tourism. Furthermore, it explored how the behavior of community residents in learning and disseminating new knowledge contributes to the reconstruction of their local identities. The findings showed that the knowledge of resource classification and evaluation of sightseeing tourism generated a paradoxical place identity, whereas the scientific and local knowledge about Danxia Mountain for tourism reconnected community residents to the place and established a place identity. The formation and changes of local residents' place identity are the result of the interactive process of knowledge's definition of place differences and the behaviors of learning and disseminating knowledge. Specifically, there are three aspects to consider: 1) Place differences and place meanings stemming from knowledge discourse. The knowledge of a place defines its differences and assigns meaning to it. Moreover, the type of knowledge of a place can change, triggering the reconstruction of the place identity of local residents. 2) Place identity arises from the learning, internalization, and construction processes of local residents in relation to place differences and meanings within the knowledge framework. This is achieved through transforming diverse individuals' experiences and feelings about a place, where meaningful and comprehensible identities are formed, leading to a diversified sense of place identity based on individual experiences. 3) Identity performance in the process of knowledge dissemination and sharing socializes individual place identities and establishes a collective place identity. This research combines knowledge as the discourse defining place differences and the behavioral interactions of using knowledge, which expands the understanding of the process and mechanisms of place identity and can provide a more comprehensive explanatory framework for establishing place identity in social-place-individual interaction. It also provides practical guidance for cultivating local residents' place identity through knowledge-based study tourism, which requires incorporating the knowledge of community residents into the heritage site's knowledge system as well as community residents as active participants in the learning and dissemination of knowledge in the context of study tourism, which is essential for fostering a sense of place identity.